2012
DOI: 10.1002/jhm.1936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyponatremia and the syndrome of inappropriate antidiuresis on mortality in elderly patients with aspiration pneumonia

Abstract: BACKGROUND:Hyponatremia is associated with pneumonia, and aspiration pneumonia is common in the elderly, however, there has been no study of hyponatremia in this population.OBJECTIVE:To determine the impact of hyponatremia on mortality in elderly patients with aspiration pneumonia, while focusing on the comparison between those with and without the syndrome of inappropriate antidiuresis (SIAD).DESIGN:Retrospective review of existing database and medical records.SETTING:A community teaching hospital in Japan.PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…Our study, which was designed to define the volaemic causation of hyponatraemia, was underpowered to compare mortality with eunatraemic pneumonia. However, we observed a trend towards higher mortality in patients with CAP and hyponatraemia when compared to eunatraemic controls, in line with previous observations …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study, which was designed to define the volaemic causation of hyponatraemia, was underpowered to compare mortality with eunatraemic pneumonia. However, we observed a trend towards higher mortality in patients with CAP and hyponatraemia when compared to eunatraemic controls, in line with previous observations …”
Section: Discussionsupporting
confidence: 93%
“…Hyponatraemia occurs in 8%‐31% of adult patients with CAP with higher incidence in children (27%‐45%) and Legionella pneumonia(44%) . Hyponatraemia in CAP is usually mild (130‐134 mmol/L) and asymptomatic, yet epidemiological data consistently demonstrate increased mortality, more frequent ITU admission, and prolonged hospital stay, in patients with CAP and hyponatraemia. Consequently, hyponatraemia in CAP has been associated with an increase in hospital costs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main admission diagnoses of nephrologic diseases in geriatrics consists of the diagnosis and management of acute/chronic renal dysfunction, UTI (upper/lower), and dyselectrolytemia. Each of these components helps determine the hospitalization outcomes in the old: dysnatremia and dyskalemia at elderly admission is associated with in-hospital mortality [43], [44], while UTI contributes to higher morbidity and mortality in the institutionalized old [45]. Furthermore, older patients have more limited renal reserve and are prone to develop AKI [46], [47].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that both SIAD and hyponatremia had negative impact in elderly patients with pneumonia. Miyashita and colleagues reported that mortality in elderly patients with aspiration pneumonia was significantly associated with SIAD [7]. A study by Nair and colleagues reported some increased risk of death with hyponatremia [8].…”
Section: Discussionmentioning
confidence: 99%